License to ILL: Do Patrons Rely on Interlibrary Loan Too Much? - Wisniewski, Rebecca; Espe, Troy (Wisconsin Association of Academic Librarians, 2019)
University of Wisconsin-Stevens Point Library fills nearly half of its interlibrary-loan article requests internally. The library owns the article, but the patron can’t — or won’t — find it. Is this problematic or positive? The poster will explore the data to examine ILL’s role in discovery.
Keywords: interlibrary loan; academic library; graduate students